Busting the Baby Teeth Myth and Increasing Children’s Consumption of Tap Water: Building Public Will for Children’s Oral Health in Colorado - Hornsby, Wyatt C.; Bailey, William; Braun, Patricia A.; Weiss, Karl; Heichelbech, James (Frontiers in Public Health, 2017)
Question Can a multifaceted statewide communications campaign motivate behavior change in low-income Colorado families to limit children’s fruit juice consumption and increase children’s consumption of tap water to prevent tooth decay? Purpose Caries is the most common chronic disease of childhood, affecting 40% of kindergartners and 55% of third graders in Colorado. Frequent consumption of 100% fruit juice is linked to childhood caries. The purpose of this campaign, “Cavities Get Around,” was to motivate families to limit children’s fruit juice consumption and increase consumption of tap water to protect baby teeth from caries, while also building public will for children’s oral health. Methods The campaign included targeted media, promotores/organizers, and family education. We focused on fruit juice because audience research showed many families view fruit juice as healthy, and it is also a common beverage among young children up to age of 6 years. We also focused on low-socioeconomic status families because data show higher childhood tooth decay rates in this population. To evaluate progress, we conducted identical pre- and post-surveys, each of 600 random low-income parents contacted by landline, mobile telephone, and Internet, allowing for comparative data. Results Significant progress was achieved compared to 2014 baseline results. Findings from a November 2015 statewide survey of parents included the following: (1) 22-point increase from 2014 in percentage of children regularly drinking tap water (from 41 to 63%). (2) 29-point decrease from 2014 in percentage of respondents who considered fruit juice consumption important to their child’s health and nutritional needs (from 72 to 43%). (3) 19-point reduction in fruit juice consumption among young children (from 66% in 2014 to 47% in 2015). (4) 6-point reduction in percentage of parents considering baby teeth “less important” than adult teeth (from 21% in 2014 to 15% in 2015). The campaign also played a role in new state rules prohibiting childcare centers from serving sugar-sweetened beverages and capping 100% juice to twice per week. Conclusion The campaign development, strategies, and evaluation results are instructive for others working on health promotion, childhood nutrition, and education interventions.